Short Communication: A small-scale coprological survey of the endoparasites in the Himalayan goral Naemorhedus goral (Hardwick, 1825) in Nepal (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Adhikari JN, Adhikari RB, Bhattarai BP, Thapa TB, Ghimire TR. 2021. Short Communication: A small-scale coprological survey of the endoparasites in the Himalayan goral Naemorhedus goral (Hardwick, 1825) in Nepal. Biodiversitas 22: 1285-1290. This study was carried out to detect the various endoparasites in the fecal samples of the Himalayan goral Naemorhedus goral (Hardwicke, 1825) from a forest patch of Rumsi area, the Seti River basin, Tanahun district, Nepal. Importantly, 17 fecal samples (89.5%) were positive for different parasites. Their positive rates showed the following orders as Strongyle (73.7%), Entamoeba sp. (52.6%), Strongyloides sp. (52.6%), Cryptosporidium sp. (26.3%), Cyclospora sp. (26.3%), Eimeria sp. (10.5%), Mullerius capillaris (10.5%), and Blastocystis sp. (5.3%). These results showed the prevalence status of the endoparasites in the Himalayan goral. This study provides general knowledge about the parasitic community using a non-invasive method. This is the first work in Himalayan goral of Nepal, hence intensive study to the other parts of Nepal is recommended.
Keywords: Coccidia, Conservation, Gastrointestinal parasites, Himalayan goral, Microscopy